The Earliest Printed Versions of the Evangelium Nicodemi and Their Manuscript Sources - Izydorczyk, Zbigniew (Apocrypha, 2011)
During the fifteenth and sixteenth centuries, the Latin Evangelium Nicodemi was printed eleven times. Five of those early editions appear to have been based on manuscripts, while the remaining six recycled earlier prints. By investigating the manuscript and print sources of those earliest editions, this paper locates the editions in the overall textual tradition of the apocryphon and reveals which textual branches provided the foundation for the reception of the Latin text in the age of print.